How the population worldwide is reacting to the COVID-19 vaccines: a systematic review on hesitancy. (20th October 2021) - Failla, G; Pantovic, A; Al-Ajlouni, Y; Ricciardi, W; Cascini, F
Abstract: Background: High rates of vaccination are worldwide required to establish a herd immunity stopping the current COVID-19 pandemic evolution. Vaccine hesitancy is a major barrier in achieving herd immunity across different populations. This study sought to conduct a systematic review of the current literature regarding attitudes and hesitancy to receiving COVID-19 vaccination worldwide. Methods: A systematic literature search was performed in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Multiple databases were searched, namely PubMed and Web of Science, on February 24th, 2021 using a set of developed keywords. Inclusion criteria included the study to be 1) conducted in English; 2) investigated attitudes, hesitancy, and/or barriers to COVID-19 vaccine acceptability among a given population; 3) utilized validated measurements techniques; 4) have the full text paper available and 5) be peer-reviewed prior to final publication. The Newcastle Ottawa (NOS) scale for cross sectional studies was used to assess the quality of the studies. Results: 73 studies were included in qualitative synthesis. Overall, vaccine acceptance rates ranged from 23.6% in Kuwait to 94.3% in Malaysia and Nepal. A variety of different factors contributed to increased hesitancy, some of which included having negative perception of vaccine efficacy, safety, convenience and price. Some of the consistent socio-demographic groups that were identified to be associated with increased hesitancy included: women, younger participants, less educated, with lower income, with no insurance, living in the rural area and self-identified as a racial/ethnic minority. Conclusions: Vaccine hesitancy rates against COVID-19 vaccine ranged widely among across different populations. Identifying the factors that interplay and result in high hesitancy rates among a population can allow formulating a directed intervention to increase their vaccination uptake rates. Key messages: It is necessary to understand the factors that contribute to the COVID-19 vaccine hesitancy. It is important to inform policy-makers and formulate direct intervention measures that will successfully handle the pandemic.